COMPARATIVE ANALYSIS OF VARIOUS FLEECE CHARACTERISTICS OF NORDUZ AND ZOM SHEEP - S. S. Tuncer; H. D. Sireli; G. Dellal (Journal of Animal and Plant Sciences, 2017)
This research aimed to evaluate the fleece samples obtained from the shoulder, rump and flank areas of Norduz and Zom sheep. The study consisted of 25 Norduz sheep and 24 Zom sheep. The longest hauteur fleece in Norduz and Zom sheep was obtained from the rump area (40.30±2.96 and 30.11±1.50 mm) and the longest barbe fleece was obtained from the rump area (58.22±4.70 and 42.28±3.10 mm). Upon examination of the fiber diameter of the fleece of the Norduz and Zom sheep, the thickest fleece was found in the rump area (35.73±1.13 and 33.01±0.86 µ), with the fleece in the other areas finer and closer together. In both breeds (Norduz and Zom), the fleece obtained from the flank had the highest elasticity (32.17±0.83 and 31.44±1.01%), and the fleece obtained from the rump had the highest strength (33.91±2.03 and 24.33±2.03 cN/tex). In both the Norduz and Zom sheep, the highest fleece yields were obtained from the flanks: 63.58±1.52 and 62.96±2.27%.  This study revealed no marked variation in the fleece yields and characteristics of the Norduz and Zom sheep, which are thought to be a variety of the White Karaman sheep.
Keywords: Sheep; Norduz; Zom; fleece characteristics